The Effect of Inward and Outward Remittances on Welfare in Africa: Array - Obiakor, Rowland Tochukwu; Akpa, Emeka; Okwu, Andy Titus (Acta Universitatis Danubius. Œconomica, 2021)
We estimated the effect of inward and outward remittances on welfare using data on 17 SSA countries from 2005 to 2019, with welfare proxied as consumption. Previous studies on remittances had tended to be focused more on the effect of inward remittances on macroeconomic variables, while few that considered inward and outward remittances were single-country analysis. The study applied the system-GMM estimation approach to accommodate the dynamic nature of the empirical model. Results showed that inward remittances exerted a positive and significant effect on consumption, while the effect of outward remittances was negative and had a significant effect. However, the coefficient of inward remittances, in absolute terms was found to be larger than the coefficient of outward remittances. The instruments used in the estimation was found to be valid by the Sargan and Hansen tests while the absence of serial correlation was confirmed by the Arrellano-Bond tests. Policy around remittances, given the greater weight of inward remittances on consumption should be such that will make remitting cheaper.